2021
DOI: 10.1002/pros.24250
|View full text |Cite
|
Sign up to set email alerts
|

Pretherapeutic estimated glomerular filtration rate predicts development of chronic kidney disease in patients receiving PSMA‐targeted radioligand therapy

Abstract: Background: Prostate-specific membrane antigen (PSMA)-targeted radioligand therapy (RLT) may be associated with renal toxicity. We aimed to identify predictive parameters for the development of chronic kidney disease (CKD) in patients with metastatic castration resistant prostate cancer (mCRPC) undergoing RLT.Methods: In 46 mCRPC patients scheduled for Lu-177-PSMA-RLT, pretherapeutic estimated glomerular filtration rate (eGFR [ml/min/1.73 m 2 ]), Tc-99mmercaptoacetyltriglycine (Tc-99m-MAG3) clearance and basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…On the other hand, a single-center retrospective trial conducted by Widjaja et al evaluated 46 mCRPC patients and found that having an abnormal pretherapeutic eGFR (<90 mL/min/1.73 m 2 ) was the strongest predictor of worsening CKD. 16 The risk of kidney injury is also supported by a phase II prospective study by Violet et al 17 where grade 1–2 renal injury was observed in 10% of patients as measured by an 11.7 mL/min reduction in renal function using [ 51 Cr]Cr-ethylenediaminetetraacetic acid (EDTA) between pretherapeutic and 3-month follow-up assessment. Our patient demonstrated no worsening of his baseline renal dysfunction, and this was likely related to optimization of his renal function with ureteric stenting, personalized dosimetry, adequate hydration during treatment, and reducing the number of [ 177 Lu]Lu-PSMA-617 cycles from six to four given his excellent response to therapy.…”
Section: Discussion and Implications For Clinical Carementioning
confidence: 92%
“…On the other hand, a single-center retrospective trial conducted by Widjaja et al evaluated 46 mCRPC patients and found that having an abnormal pretherapeutic eGFR (<90 mL/min/1.73 m 2 ) was the strongest predictor of worsening CKD. 16 The risk of kidney injury is also supported by a phase II prospective study by Violet et al 17 where grade 1–2 renal injury was observed in 10% of patients as measured by an 11.7 mL/min reduction in renal function using [ 51 Cr]Cr-ethylenediaminetetraacetic acid (EDTA) between pretherapeutic and 3-month follow-up assessment. Our patient demonstrated no worsening of his baseline renal dysfunction, and this was likely related to optimization of his renal function with ureteric stenting, personalized dosimetry, adequate hydration during treatment, and reducing the number of [ 177 Lu]Lu-PSMA-617 cycles from six to four given his excellent response to therapy.…”
Section: Discussion and Implications For Clinical Carementioning
confidence: 92%
“…Patients exhibiting impaired renal function, extensive prior chemotherapy, or prolonged hematological toxicity may have a higher susceptibility to experiencing more severe myelotoxicity [50]. There is limited clinical data on patients with moderately impaired renal function (GFR 30-50 mL/min), suggesting a gap in understanding the full impact of 177 LuPSMA radioligand therapy in this subgroup [51,52]. In cases where patients began 177 LuPSMA radioligand therapy with already dimini shed kidney function, worsening renal conditions were observed, though these could also be attributed to the typical risk factors associated with chronic kidney disease [52,53].…”
Section: Treatment-related Toxicity Of Psma Radioligand Therapymentioning
confidence: 99%
“…There is limited clinical data on patients with moderately impaired renal function (GFR 30-50 mL/min), suggesting a gap in understanding the full impact of 177 LuPSMA radioligand therapy in this subgroup [51,52]. In cases where patients began 177 LuPSMA radioligand therapy with already dimini shed kidney function, worsening renal conditions were observed, though these could also be attributed to the typical risk factors associated with chronic kidney disease [52,53]. These observations indicate a crucial need for careful patient selection and monitoring within MDT, particularly for those with preexisting conditions that might elevate the risk of adverse outcomes from radioligand therapy.…”
Section: Treatment-related Toxicity Of Psma Radioligand Therapymentioning
confidence: 99%